CCL20 neutralization by a monoclonal antibody in healthy subjects selectively inhibits recruitment of CCR6+ cells in an experimental suction blister. (22nd April 2017) - Bouma, Gerben; Zamuner, Stefano; Hicks, Kirsty; Want, Andrew; Oliveira, João; Choudhury, Arpita; Brett, Sara; Robertson, Darren; Felton, Leigh; Norris, Virginia; Fernando, Disala; Herdman, Michael; et al.
Abstract : Aims: GSK3050002, a humanized IgG1κ antibody with high binding affinity to human CCL20, was administered in a first‐in‐human study to evaluate safety, pharmacokinetics (PK) and pharmacodynamics (PD). An experimental skin suction blister model was employed to assess target engagement and the ability of the compound to inhibit recruitment of inflammatory CCR6 expressing cells. Methods: This study was a randomized, double‐blind (sponsor open), placebo‐controlled, single‐centre, single ascending intravenous dose escalation trial in 48 healthy male volunteers. Results: GSK3050002 (0.1–20 mg kg −1 ) was well tolerated and no safety concerns were identified. The PK was linear over the dose range, with a half‐life of approximately 2 weeks. Complex of GSK3050002/CCL20 increased in serum and blister fluid with increasing doses of GSK3050002. There were dose‐dependent decreases in CCR6 + cell recruitment to skin blisters with maximal effects at doses of 5 mg kg −1 and higher, doses at which GSK3050002/CCL20 complex in serum and blister fluid also appeared to reach maximum levels. Conclusions: These results indicate a relationship between PK, target engagement and PD, suggesting a selective inhibition of recruitment of CCR6 + cells by GSK3050002 and support further development of GSK3050002 in autoimmune and inflammatory diseases.